Bond behaviour of CFRP tendons in UHPFRC. (1st January 2019) - Stark, Alexander; Classen, Martin; Hegger, Josef
Highlights: Discussion of pull-out tests and tests on the transfer length using CFRP tendons and UHPFRC. Discussion of results using non-linear finite element analysis to derive parameters for friction laws and predict transfer lengths. Discussion of results using a thick-walled cylinder model to predict transfer lengths and cracking of concrete. Discussion of results of parametric studies. Abstract: For a safe design of prestressed concrete members, the bond behaviour of prestressing tendons needs to be investigated. In general, for prestressing tendons, an a priori determination of the transfer length is essential. For thin concrete elements, the minimum thickness to provide a split-free transmission zone has to be determined. To realise thin concrete members, high performance cementitious composites are advantageous. Ultra-high performance fibre reinforced concrete (UHPFRC) provides high compressive and tensile strengths with ductile material behaviour. The application of non-corrosive reinforcement, e.g. carbon fibre reinforced polymer (CFRP), allows for filigree concrete elements with a thin concrete cover to only fulfil bond requirements. For the material combination of CFRP reinforcement and UHPFRC, the bond behaviour was investigated experimentally and theoretically. By means of pull-out tests local bond strengths were determined for different release states of jacking forces (i.e. lateral extension of the reinforcement). Tests on small-scale beams were conducted to determine transfer lengths and minimum dimensions of thin UHPFRC elements for two types of CFRP prestressing tendons. Simulations and further investigations on the bond behaviour were performed using non-linear finite element modelling as well as an analytical approach.